A novel endoscopic submucosal dissection technique for proton pump inhibitor-refractory gastroesophageal reflux disease. (December 2014) - Ota, Kazuhiro; Takeuchi, Toshihisa; Harada, Satoshi; Edogawa, Shoko; Kojima, Yuichi; Inoue, Takuya; Higuchi, Kazuhide
Abstract Objectives: Although drug treatment is the usual first-line therapy for gastroesophageal reflux disease (GERD), not all patients receive satisfactory relief from drug therapy, alone. We developed an endoscopic fundoplication technique using endoscopic submucosal dissection (ESD); the technique is referred to as ESD for GERD (ESD-G). This study investigated the safety and efficacy of this novel technique in patients with drug-refractory GERD. Patients and methods: ESD-G narrows the hiatal opening through ESD of the esophagogastric junction (EGJ) mucosa. For safety reasons, the range of mucosal resection was limited to half (1/2 or 1/4 +1/4) of the circumference of the EGJ lumen. ESD-G was performed on 13 patients with proton pump inhibitor (PPI)-refractory GERD. GERD symptoms, PPI dose, and 24-h esophageal pH monitoring results were compared before and 6 months after the procedure. Results. In 12 cases, symptoms significantly improved after ESD-G. Five patients demonstrated improved esophagitis, three were able to discontinue PPI therapy, and three were able to reduce their PPI dosage following surgery. The esophageal pH <4 holding time ratio was also decreased after ESD-G. Conclusions. ESD-G may be useful for PPI-refractory GERD patients.